2013
DOI: 10.1093/jnci/djt006
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Primitive Chronic Myeloid Leukemia Cells by Effective Inhibition of a New AHI-1–BCR-ABL–JAK2 Complex

Abstract: BackgroundImatinib mesylate (IM) induces clinical remission of chronic myeloid leukemia (CML). The Abelson helper integration site 1 (AHI-1) oncoprotein interacts with BCR-ABL and Janus kinase 2 (JAK2) to mediate IM response of primitive CML cells, but the effect of the interaction complex on the response to ABL and JAK2 inhibitors is unknown.MethodsThe AHI-1–BCR-ABL–JAK2 interaction complex was analyzed by mutational analysis and coimmunoprecipitation. Roles of the complex in regulation of response or resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 69 publications
1
79
0
Order By: Relevance
“…Because of the BCR-ABL-independent nature of MHC-II downregulation, combination therapies of JAK inhibitors with TKI could target the disease bulk and the LSCs. 39,48 Indeed, recent studies demonstrate synergy between RUX and NIL, inducing apoptosis in CML LSCs. 49 Our studies could suggest that LSCs remaining after dual RUX/TKI treatment may have a reduced ability to evade host immunity because of re-expression of MHC-II.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the BCR-ABL-independent nature of MHC-II downregulation, combination therapies of JAK inhibitors with TKI could target the disease bulk and the LSCs. 39,48 Indeed, recent studies demonstrate synergy between RUX and NIL, inducing apoptosis in CML LSCs. 49 Our studies could suggest that LSCs remaining after dual RUX/TKI treatment may have a reduced ability to evade host immunity because of re-expression of MHC-II.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Perez et al demonstrated the DNA methylation pattern to be similar in chronic phase PV, ET and PMF, and differentially methylated genes were mostly enriched in the NF-κB pathway. 17 They also noted that in MPN patients who transform to AML, the number of differentially methylated regions increased significantly and the aberrant genes were involved in the 'interferon pathway' or were represented by genes already reported in de novo AML. Collectively, these efforts suggest underlying epigenome differences between the MPN subtypes with potential clinical impact, and provide motivation for the use of hypomethylating and other novel agents targeting the epigenome in the MPNs.…”
Section: Unraveling the Impact Of Epigenetics In The Classical Mpnsmentioning
confidence: 97%
“…18,19 25 Pharmacologic interference with the JAK2/STAT5 pathway, therefore, represents an attractive therapeutic strategy in CML; however, STAT5 is a difficult drug target as it lacks an enzymatic domain and a simpler approach to interfere with STAT5 function is to inhibit its predominant activating kinase, JAK2.…”
Section: Introductionmentioning
confidence: 99%